Mind Over Media: Moderasi Literasi Keuangan dalam Pengaruh Finfluencer dan FOMO terhadap Keputusan Investasi pada Investor Pemula - Lidya Anastasya; Achmad Ridha; Wiwin Riski Windarsari (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2025)
This study examines the influence of finfluencers and fear of missing out (FOMO) on investment decisions among novice investors, with financial literacy as a moderating variable. The rise of social media has made finfluencers and FOMO dominant social and emotional factors in digital investing. Using a quantitative causal approach with SEM-PLS on 100 novice investors from digital platforms, the results show that both finfluencer and FOMO positively affect investment decisions. Financial literacy significantly moderates the effect of finfluencers but does not significantly moderate the relationship between FOMO and investment decisions. The findings indicate that digital investment behavior is driven by the interaction of social, emotional, and cognitive factors, with financial literacy enhancing rational evaluation of financial information. Keywords: finfluencer, fear of missing out (FOMO), financial literacy, investment decision